New University Educational Space: Integration of Education and Science - Maslennikova, Ludmila V.; Maykova, Svetlana E.; Okunev, Denis V. (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the work is to study the new components of the educational space, which is formed on the basis of the integration of educational and scientific activities of research universities. The main aim of the article is evaluation of the effectiveness of the integration of science and education in the new educational space in research universities from the standpoint of forming a complex of unique scientific, research and entrepreneurial competences, both university staff and students.Design/Methodology/Approach – The main research methods are content analysis of the concept of educational space and system analysis of its main components.Findings – The relationship between improving the efficiency of research activities and the formation of a high level of competence of staff and students of the university has been revealed. The synthesis of new opportunities created in modern research universities ensures the formation of a unique set of students' competencies.Originality/Value – Taking into account the insufficient elaboration of the problem area of cultivating the educational space of the research university, there has been taken the attempts not only to identify new components of the educational space of the university, but also to justify the need to include them in the field of formation of students' unique competences, including scientific, research and entrepreneurial ones.